KECERDASAN EMOSIONAL DAN KONTROL DIRI SISWA SMK LABOR BINAAN FKIP UNRI PEKANBARU - Syafri, Bayu Saputra; Umari, Tri; Yakub, Elni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: In the world of education that affects various aspects one of them is emotional intelligence and self-control that can harm other people and students themselves. This study aims to determine the emotional intelligence and self-control students in schools, as well as to determine the emotional intelligence of students in relation to student self-control. This research type is descriptive research. Population in this research is all class X student counted 6 class with total 210 student. sample size 165 students taken 75% of the population members. This study can be concluded that: 1) Emotional intelligence of students more than half are in the high category. With the most choices on self-regulation and motivation aspects of the highest score. Emotional intelligence of female students is higher than male students, 2) Student self-control is almost entirely in the high category. With the most choice on decision control aspects and cognitive control aspects at the highest score. Self-control of female students is higher than that of male students, and 3) Emotional intelligence of students in relation to student self-control is the highest emotional intelligence is in high self-control category, and emotional intelligence is in high self-control category.Keywords: Emotional Intelligence, Self Control